1996
DOI: 10.1016/0014-5793(96)00822-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cathepsin B by its propeptide: Use of overlapping peptides to identify a critical segment

Abstract: Ten overlapping 15-mer peptides (peptidyl amides) spanning the proregion of rat cathepsin B (residues lp-60p) were constructed to identify minimal segments having inhibitory activity towards the mature enzyme, that could be used to develop a new generation of peptide-derived inhibitors specifically targeting the active site of the corresponding proteinase. Three synthetic peptides, containing the pentapeptide Leu-CysGly-Thr-Val (residues 41p-45p) in their sequence, inhibited cathepsin B with Ki values in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…4 ported to be inhibited most strongly by the N-terminal basic segment of the propeptide (41), whereas a lysine residue in the C-terminal region of the propeptide is known to interact with the active site 2 aspartic acid residues in the pepsinogen molecule (43). As for cathepsin B, two separate 5-6-residue peptide segments in the central region of the propeptide and a cysteine residue in one of these segments, which is assumed to interact with the oxyanion hole at the active site of the enzyme, were suggested to be important for the inhibition (14,42). In proproptein convertases, the importance for inhibition was reported for the peptide fragments from the C terminus of each propeptide and especially for the C-terminal seven residues corresponding to the P1-P7 positions relative to the autocatalytic cleavage site (23)(24)(25).…”
Section: Thermal Stabilization Of Agp By Truncated Propeptides and Almentioning
confidence: 99%
See 1 more Smart Citation
“…4 ported to be inhibited most strongly by the N-terminal basic segment of the propeptide (41), whereas a lysine residue in the C-terminal region of the propeptide is known to interact with the active site 2 aspartic acid residues in the pepsinogen molecule (43). As for cathepsin B, two separate 5-6-residue peptide segments in the central region of the propeptide and a cysteine residue in one of these segments, which is assumed to interact with the oxyanion hole at the active site of the enzyme, were suggested to be important for the inhibition (14,42). In proproptein convertases, the importance for inhibition was reported for the peptide fragments from the C terminus of each propeptide and especially for the C-terminal seven residues corresponding to the P1-P7 positions relative to the autocatalytic cleavage site (23)(24)(25).…”
Section: Thermal Stabilization Of Agp By Truncated Propeptides and Almentioning
confidence: 99%
“…These roles, however, have not yet been fully understood, and further studies on various proteins are necessary. As for the inhibitory properties of the propeptides of peptidases, there are numbers of reports describing their inhibition profiles and type of inhibition (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, only a few attempts have been made so far to identify critical sequences and/or residues in the propeptide important for inhibition of the corresponding mature peptidase, and much of the inhibition mechanisms, the structural determinants in the propeptide, and the sites of binding involved in the inhibition remains to be established.…”
mentioning
confidence: 99%
“…The relative contribution of each region of cathepsin L propeptide to binding to mature enzyme has been measured by successive truncations of the recombinant propeptide (25,26). We have used a different approach, based on the construction of synthetic peptides overlapping the sequence of the prosegment of cathepsin B, to identify the critical residues interacting with the active site of the mature enzyme (27). But the primary sequences of the proregion of parasite cysteine proteinases differ significantly from those of their mammalian and plant homologues, raising the question of whether the proteolytic activity of parasite proteinases is similarly regulated by their proregion.…”
mentioning
confidence: 99%
“…Peptides Pcp24, Pcp25, Pcp26, Pcp27, Pcp32, and Pcp33 were analyzed by reverse phase-HPLC (Brownlee C18 OD 300 column) as indicated above. (27). The peptide HIV1-V3-13 is derived from the V3 loop of Gp120 (29).…”
mentioning
confidence: 99%
“…23) Chagas et al constructed 10 overlapping 15-mer peptidyl amides spanning the proregion of rat cathepsin B to identify the minimal segments with inhibitory activity toward the mature enzyme. 24) Three synthetic peptidyl amides containing the pentapeptide LCGTV, f(41-45) of rat procathepsin B, inhibited cathepsin B. They also reported that the peptidyl amide, f(36-50) of rat procathepsin B, showed the most potent inhibition and that the Cys-42 region might be essential because alkylation at this residue resulted in rapid proteolytic degradation of the peptide.…”
Section: Discussionmentioning
confidence: 99%